Restarting Anticoagulant Treatment After Intracranial Hemorrhage in Patients With Atrial Fibrillation and the Impact on Recurrent Stroke, Mortality, and Bleeding. Issue 6 (11th August 2015) - Nielsen, Peter Brønnum; Larsen, Torben Bjerregaard; Skjøth, Flemming; Gorst-Rasmussen, Anders; Rasmussen, Lars Hvilsted; Lip, Gregory Y.H.
<x xml:space="preserve">Abstract</x> Background— Intracranial hemorrhage is the most feared complication of oral anticoagulant treatment. The optimal treatment option for patients with atrial fibrillation who survive an intracranial hemorrhage remains unknown. We hypothesized that restarting oral anticoagulant treatment was associated with a lower risk of stroke and mortality in comparison with not restarting. Methods and Results— Linkage of 3 Danish nationwide registries in the period between 1997 and 2013 identified patients with atrial fibrillation on oral anticoagulant treatment with incident intracranial hemorrhage. Patients were stratified by treatment regimens (no treatment, oral anticoagulant treatment, or antiplatelet therapy) after the intracranial hemorrhage. Event rates were assessed 6 weeks after hospital discharge and compared with Cox proportional hazard models. In 1752 patients (1 year of follow-up), the rate of ischemic stroke/systemic embolism and all-cause mortality (per 100 person-years) for patients treated with oral anticoagulants was 13.6, in comparison with 27.3 for nontreated patients and 25.7 for patients receiving antiplatelet therapy. The rate of ischemic stroke/systemic embolism and all-cause mortality (per 100 person-years) for recurrent intracranial hemorrhage, the rate of ischemic stroke/systemic embolism, and all-cause mortality (per 100 person-years) patients treated with oral anticoagulants was 8.0, in comparison with 8.6 for nontreated patients and 5.3 for patients receiving antiplatelet therapy. The adjusted hazard ratio of ischemic stroke/systemic embolism and all-cause mortality was 0.55 (95% confidence interval, 0.39–0.78) in patients on oral anticoagulant treatment in comparison with no treatment. For ischemic stroke/systemic embolism and for all-cause mortality, hazard ratios were 0.59 (95% confidence interval, 0.33–1.03) and 0.55 (95% confidence interval, 0.37–0.82), respectively. Conclusions— Oral anticoagulant treatment was associated with a significant reduction in ischemic stroke/all-cause mortality rates, supporting oral anticoagulant treatment reintroduction after intracranial hemorrhage as feasible. Future trials are encouraged to guide clinical practice in these patients.